How Does AI Analyze Genomic Data for Personalized Treatment? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2022)
Personalized medicine, which aims to tailor medical treatment to the individual characteristics of each patient, is no longer a futuristic concept. At the he...
Keywords: Precision Medicine and Genomics; Analyze; Genomic; Personalized; Artificial Intelligence; Machine Learning; Deep Learning